source 2007 Hisil--Carter--Dawson
assume X2 = 1
compute S0 = Y2^2
compute S1 = Z2^2
compute S2 = (Y2+Z2)^2-S0-S1
compute S3 = 2 Y2
compute S4 = 2 Z2
compute R0 = X1^2
compute R1 = Y1^2
compute R2 = Z1^2
compute R3 = X1+Y1
compute Y3 = Y1+Z1
compute Y3 = Y3^2
compute Z3 = X1+Z1
compute Z3 = Z3^2
compute X3 = R3^2
compute R3 = Y3-R1
compute R3 = R3-R2
compute Y3 = R0 S2
compute Y3 = Y3-R3
compute R3 = X3-R0
compute R3 = R3-R1
compute Z3 = Z3-R0
compute Z3 = Z3-R2
compute X3 = R1 S4
compute R0 = Z3 S0
compute X3 = X3-R0
compute Z3 = R2 S3
compute R0 = R3 S1
compute Z3 = Z3-R0